Testing Weak-Form Market Efficiency of Dhaka Stock Exchange - Hasan‬‬‬‬‬‬‬‬, Md.‬ Abu (Global Disclosure of Economics and Business, 2015)
Measuring the efficiency of the stock market is an important research topic as there are various implications for investors. This paper investigates the weak form efficiency in the framework of the random walk hypothesis for the stock market in Bangladesh, employing both Non Parametric tests (Runs test and Phillips-Perron test) and Parametric tests (Autocorrelation test, Augmented Dickey-fuller test, and Variance Ratio test). The study uses daily return data for the three stock indices of Dhaka Stock Exchange such as DSI (from 02 January 1993 to 27 January 2013) with a total of 4823 daily return observations, DGEN (from 01 January 2002 to 31 July 2013) with a total of 2903 daily return observations, and DSE-20 (from 01 January 2001 to 27 January 2013) with a total of 3047 daily return observations. The evidence suggests that all the return series do not follow the random walk model, and thus the Dhaka Stock Exchange is inefficient in weak form. Thus, historical stock prices can be used to achieve superior gains from the stock markets in Bangladesh.JEL Classification Code: C22, G10, G14